Nanobioprospecting of photoautotrophs for the fabrication of quantum dots: mechanism and applications - Pandya, Pranav; Webster, Thomas J.; Ghosh, Sougata (Frontiers in Chemistry, 2024)
Quantum dots (QDs), also known as nanoparticle-based fluorescent probes, are luminescent semiconductor particles with a size range of 2 to 20 nm. The unique optical and electronic capabilities of QDs have led to expanded applications in several fields such as optoelectronics, transistors, sensors, photodetection, catalysis, and medicine. The distinct quantum effects of nanocrystals can be controlled by changing their sizes and shapes using a variety of top-down and bottom-up tactics. QDs were traditionally fabricated using complex, expensive, toxic, and aggressive chemical techniques, which limited their application in a variety of disciplines. A unique approach for the biosynthesis of nanomaterials has been devised, which employs living organisms in the synthesis process and adheres to green chemistry principles. Biogenic QDs have favorable physicochemical features, biocompatibility, and fewer cytotoxic effects as a result of using natural biomolecules and enzymatic processes for mineralization, detoxification, and nucleation of metals and nonmetals to synthesize QDs. This is the first comprehensive review of its kind that highlights the synthesis of several doped and undoped QDs, including graphene QDs, carbon dots, silicon QDs, N/S-CDs, silver-CDs, cadmium-selenium QDs, and zinc oxide QDs, exclusively using photoautotrophic algae and plants. The different plausible mechanisms behind phyco- and phyto-fabrication of QDs are also discussed in detail along with their applications that include detection of organic and inorganic compounds, degradation of hazardous dyes, free radical scavenging, antimicrobial activity, cytotoxicity and bioimaging. Thus, this review aims to give valuable insights for the rational fabrication of photoluminescent nanomaterials with tunable structural and functional properties.